Penyusunan Model Pengamanan Aset Tidak Bergerak di Kabupaten Sumenep - Toton Merianto; Siti Musyarofah; Bambang Haryadi (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
The problem of management asset is one of many problems faced by local government whose material asset. The research purpose is to create security model on immovable assets in Sumenep. This research uses qualitative method with soft system methodology approach. The results showed that Sumenep district government in implementing the immovable asset security is not optimal because there is no standard reference, so immovable assets security model is needed. Administrative security model starting from demand the land assets report from the entire agencies accompanied by supporting documents. Furthermore, the report synchronized and verified directly to the assets location. If there are assets that administratively incomplete, than it must performed by legal security that starts from tracking the land assets status, if uncertified assets are found than certification is needed. Certified land assets then followed up through the physical security of land assets that used by the other party or misused by parties who violate the provisions of the land use agreement by fencing/installing a sign of ownership